Debt stabilizing fiscal rules - Philippe Michel; Leopold von Thadden; Jean-Pierre Vidal (European Central Bank (ECB), 2006)
Unstable government debt dynamics can typically be corrected by various fiscal instruments, like appropriate adjustments in government spending, public transfers, or taxes. This paper investigates properties of state-contingent debt targeting rules which link stabilizing budgetary adjustments around a target level of long-run debt to the state of the economy. The paper establishes that the size of steady-state debt is a key determinant of whether it is possible to find a rule of this type which can be implemented under all available fiscal instruments. Specifically, considering linear feedback rules, the paper demonstrates that there may well exist a critical level of debt beyond which this is no longer possible. From an applied perspective, this finding is of particular relevance in the context of a monetary union with decentralized fiscal policies. Depending on the level of long-run debt, there might be a conflict between a common fiscal framework which tracks deficit developments as a function of the state of the economy and the unrestricted choice of fiscal policy instruments at the national level.
Keywords: E63; H62; 330; fiscal regimes; overlapping generations; Öffentliche Schulden; Haushaltsdefizit; Haushaltskonsolidierung; Finanzpolitik; Geldpolitik; Theorie; Eurozone